Peningkatan Tes Kemampuan Bahasa Inggris (TOEFL) untuk Dosen Eligible Sertifikasi Pendidik di IAHN Gde Puja Mataram - Anggrawan, Anthony; Kamil, Wahyu; Primajati, Gilang; Herawati, Baiq Candra; Suhendra, Erwin (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
The Basic Academic Ability Test (TKDA) has a very important role to measure, mapping, and acquire quality Human Resources (HR) based on one's basic abilities in academic scholarship. These basic academic abilities and skills test the ability to think logically, systematically, and critically. This TKDA is often used for various purposes related to academic scores, such as in recruitment to enter the world of work, in the selection of new student admissions, and for eligibility requirements for lecturer certification (SERDOS). The government lecturer certification requires lecturers who are qualified serdos to have a TKDA ability score with a minimum threshold of 530 for 2022. This threshold continues to increase every year for 2021 the threshold is still 430. This increase in the threshold is intended to obtain lecturer standards better from year to year. Therefore, capacity building for eligible lecturers must be carried out with a systematic training scheme. Of course, it is an obligation to be able to continue until the assessment stage by the assessor in order to achieve the target that has been set. This community service, especially for the lecturers, is very useful for improving their abilities. The material given by the tutors who of course have passed the serdos is about TKDA knowledge itself such as types of test questions, solving tricks, test rules, how to make the test time more efficient, and finally the TKDA simulation tryout. Based on the results of the overall evaluation, it can be seen that the main target of the training implementation has been achieved. Participants better understand, understand, and have strategies to deal with TKDA, and based on the simulation, participants are able to work on TKDA questions well.